Vaginal Hysterectomy with Anterior Four-Arm Mesh Implant Technique in the Surgical Treatment of a Woman with Total Pelvic Organ Prolapse and Urinary Incontinence: A Case Report and Review of the Literature - Gökmen Sukgen; Esra Saygılı Yılmaz; Eralp Başer (Hindawi Limited, 2016)
Purpose. We present a case report of a woman with total POP and SUI who was treated with a technique utilizing vaginal hysterectomy followed by the placement of a four-arm synthetic polypropylene mesh implant system. Methods. An 81-year-old grand-multiparous woman presented to our clinic complaining of a vaginally protruding mass and urinary incontinence. A surgical approach including vaginal hysterectomy, anterior four-arm mesh implant, posterior large segment vaginal enterocele repair, and perineoplasty with levator ani fixation was planned. Results. The patient was discharged home at the second postoperative day. Follow-up visits at the first, 3rd, and 6th months were normal. There was complete symptomatic relief and objective cure of the POP and urinary incontinence symptoms. Conclusion. We believe that anterior four-arm mesh implant and large posterior repair should be considered after vaginal hysterectomy. Future studies are needed to evaluate the utility of this technique for treatment of POP.